EP682 Laparoscopic ovarian transposition in non-gynaecological cancers: more than just oncological outcomes. (1st November 2019) - Shylasree, T; Singh, P; Engineer, R; Saklani, A; D'souza, A; Khanna, N; Lasker, S
Abstract : Introduction/Background: Pelvic radiation leads to permanent ovarian failure. Laparoscopic ovarian transposition (LOT) is an established surgical technique to salvage ovaries. The success rate of LOT varies widely and is quoted between 40 to 80% in gynecological cancers In non-Gynecological cancers the available data is limited. We present the data on LOT performed for non-gynecological cancers from a tertiary cancer hospital. Aims: Analyze the effectiveness of LOT in non-gynaecological cancers. Methodology: Forty seven patients who underwent LOT during the years 2013 to 2018 (40 with rectal cancer and 7 with non-rectal cancer mainly pelvic childhood sarcomas and lymphoma) were retrieved from a prospectively maintained data base. Disease characteristics, oncological outcomes and return of menstrual function were analyzed. Results: Median age of patient was 25 years (range 8–35 years). 53% patients were unmarried. Median postoperative stay was 48 hours and postoperative course uneventful in all patients. Of the 40 rectal cancers, 22 had adenocarcinoma and 18 signet ring pathology. 19% patient underwent stoma formation along with ovarian transposition. There was no delay in definitive treatment due to LOT procedure. At the time of analysis a total of 20 patient were excluded. (13 patients had died, 3 defaulted, 2 premenstrual and 2 had progressive disease on CTRT requiring removal of ovaries/uterus). Twenty eight patients were eligible for evaluation, out of which 60.7% were disease free and 53.5% were menstruating. Conclusion: Laparoscopic ovarian transposition is safe and does not delay primary treatment. Of the the evaluable patients more than half resumed regular menstrual function. Fertility chances and issues will become apparent with long term follow up of the cohort as the uterus also gets irradiated during pelvic radiation. Disclosure: Nothing to disclose.